A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Full Ranking Method in Data Envelopment Analysis with Multi-Criteria Decision Analysis - Tavana, Madjid; Bonyani, A.; Karimi, T. (International Journal of Applied Management Science)

A new mathematical formulation for the simultaneous optimization of charging infrastructure and vehicle schedules for electric bus systems - Stumpe, Miriam (Transportation Research Procedia)

A Novel Fuzzy General Best-Worst Method for Considering Diversity and Inclusion in Supplier Selection Programs - Tavana, Madjid; Sorooshian, S.; Sarvarizadehkouhpaye, M.; Mina, H. (Annals of Operations Research)

A systematic review of the soft computing methods shaping the future of the metaverse - Tavana, Madjid; Sorooshian, Shahryar (Applied Soft Computing)
Keywords: Software

A Two-Level Supply Chain Coordination Model for Perishable Products under Optimal Markdown Time and Trade Credit Policies - Setak, M.; Tavana, Madjid; Talafi Daryani, H. (OPSEARCH)

Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

An early indicator for anomalous stock market performance - Fritz, Marlon; Gries, Thomas; Wiechers, Lukas (Quantitative Finance)
We propose an indicator for detecting anomalous stock market valuation in real time such that market participants receive timely signals so as to be able to take stabilizing action. Unlike existing approaches, our anomaly indicator introduces three methodological novelties. First, we use an endogenous, purely data-driven, nonparametric trend identification method to separate long-term market movements from more short-term ones. Second, we apply SETAR models that allow for asymmetric expansions and contractions around the long-term trend and find systematic stock price cycles. Third, we implement these findings in our indicator and conduct real-time market forecasts, which have so far been neglected in the literature. Applications of our indicator using monthly S&P 500 stock data from 1970 to the end of 2022 show that short-term anomalous market movements can be identified in real time up to one year ahead. We predict all major anomalies, including the 1987 Bubble and the initial phase of the Financial Crisis that began in 2007. In total, our anomaly indicator identifies more than 80% of all – even minor – anomalous episodes. Thus, smoothing market exaggerations through early signaling seems possible.
Keywords: General Economics; Econometrics and Finance; Finance

An Integrated Fuzzy Analytic Network Process and Fuzzy Regression Method for Bitcoin Price Prediction - Amiri, Arman; Tavana, Madjid; Arman, Hosein (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Anwendung von System Dynamics zur Geschäftsmodellinnovation in einem B2B-Ökosystem - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Digitale Plattformen und Ökosysteme im B2B-Bereich)

Can leaders motivate employees’ energy-efficient behavior with thoughtful communication? - Hoffmann, Christin; Thommes, Kirsten (Journal of Environmental Economics and Management)
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Data Envelopment Analysis: From Non-Monotonic to Monotonic Scale Elasticities - Dellnitz, A.; Tavana, Madjid (European Journal of Operational Research)

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

Designing taxi ridesharing systems with shared pick-up and drop-off locations: Insights from a computational study - Stumpe, Miriam; Dieter, Peter; Schryen, Guido; Müller, Oliver; Beverungen, Daniel (Transportation Research Part A: Policy and Practice)

Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

Die Leiden des jungen (Datenaus-) Werthers - Einblicke in die Praxis der empirischen Rechtsforschung - Bartlitz, David (Rechtstatsachen im Privatrecht)

Digitale Plattformen und Ökosysteme im B2B-Bereich - Fallstudien, Ansätze, Technologien und Tools
Das Herausgeberwerk präsentiert aktuelle Forschungsergebnisse und praktische Erkenntnisse aus dem Bereich von digitalen Plattformen und Ökosystemen im Business-to-Business-Kontext. Dabei liegt der Schwerpunkt auf empirischen und konzeptionellen Beiträgen. Neben Grundlagen, Enablern und Fallstudien werden ebenso mögliche Vorgehensweisen zur Entwicklung von Plattformen behandelt. Praktikerinnen und Praktiker aus den Bereichen Management, Strategische Planung und Business Development erhalten Impulse, um Digitale Plattformen und Ökosysteme erfolgreich voranzutreiben und so Potenziale innerhalb ihres Unternehmens zu realisieren. Forschende, Lehrende und Studierende aus den Bereichen Digitale Plattformen und Ökosysteme aus dem Business-to-Business-Kontext dienen die Beiträge als Anregung für intensive Diskussionen.

Do Country Risk Factors Attenuate the Effect of Tax Loss Incentives on Corporate Risk-Taking? - Osswald, Benjamin; Sureth-Sloane, Caren
This study investigates whether country risk factors, including political and fiscal budget risk, attenuate the effectiveness of tax policy tools that aim to encourage corporate risk-taking. Exploiting a cross-country panel, we predict and find that the effectiveness of loss offset rules and tax rate changes is fully attenuated for firms located in high-risk countries. We document the attenuating effect of country risk is more pronounced in high-tax countries or when countries increase their corporate tax rate. Additional tests around the U.S. federal budget crises from 2011 to 2013 indicate that temporarily heightened fiscal budget risk attenuates the effectiveness of loss offset rules even in countries with low political risk. We identify conditions (low political and low fiscal budget risk) under which targeted tax policy tools effectively stimulate risk-taking. This suggests that ensuring taxpayers receive tax refunds is important in times of economic crises with budgetary or political challenges.

Einführung - Wortmann, Fabio; Kämmerling, Sina; Hemmrich, Simon; Gradert, Till; Ellermann, Kai (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Einführung in das Bürgerliche Recht

Gesetz über digitale Märkte (Digital Markets Act) - Bartlitz, David; Gräfe, Alexander (Handbuch des EU-Wirtschaftsrechts)

Green Multi-Objective Scheduling - A memetic NSGA-III for flexible production with real-time energy cost and emissions - Burmeister, Sascha Christian

Grundlagen - Hemmrich, Simon; Wortmann, Fabio; Lüttenberg, Hedda; Gradert, Till; Kämmerling, Sina; Meyer, Maurice (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Hierarchical Taxonomies in Information Systems - Nickerson, Robert C.; Varshney, Upkar; Muntermann, Jan; Kundisch, Dennis (Proceedings of Thirtieth Americas Conference on Information Systems (AMCIS))

Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Knowledge by Design in Education - Brase, Alexa Kristin; Jenert, Tobias (EDeR. Educational Design Research)
The editorial introduces the special issue Knowledge by Design in Education: Key challenges and experiences from research practice, posing key questions, offering an insight into ongoing discussions, and presenting an overview of the included articles.

Komplexität von Verrechnungspreisen und Tax Compliance: Einblicke in deutsche Unternehmen - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Leveraging Business Modeling Tools For Ecosystemic Business Model Design - Vorbohle, Christian; Kundisch, Dennis (Journal of Business Models)

Moment or movement – the heterogeneous impact of the Black Lives Matter movement on personal and societal charitable crowdfunding campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Internet Research)

On the Capacity of Artificial Intelligence Techniques and Statistical Methods to Deal with Low Quality Data in Medical Supply Chain Environments - Santos-Arteaga, F.J.; Di Caprio, D.; Tavana, Madjid; Cucchiari, D.; Campistol, J.M.; Oppenheimer, F.; Diekmann, F.; Revuelta, I. (Engineering Applications of Artificial Intelligence)

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

Rechtstatsachen im Privatrecht

Speedup and efficiency of computational parallelization: A unifying approach and asymptotic analysis - Schryen, Guido (Journal of Parallel and Distributed Computing)

Tax Compliance Management Systeme in deutschen Betriebsprüfungen – Eine Analyse praktischer Erfahrungen - Schulz, Kim Alina; Sureth-Sloane, Caren (Steuer und Wirtschaft)

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))
Excellent Information Systems (IS) bachelor or master student theses have the potential to inform the scientific community about interesting findings about IS phenomena. However, transforming such theses into scientific working papers is not only time-consuming for the student and the supervisor, but also purely voluntary. Part of the problem is that few IS faculties offer any structured course for the transformation process as part of their curriculum. This significantly reduces the proportion of outstanding theses that are developed into working papers and, ultimately, into publications, resulting in a loss of knowledge for the broader IS community. To address this structural deficit, we aim to develop and implement a credit course and open educational resources (e.g., course schedule, slides, videos) that support students in developing their theses into publishable scientific research papers. This approach not only enriches the scientific discourse but also presents a research-oriented educational disruption for the IS community.
Keywords: Student Thesis; Scientific Publishing; Course Implementation

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

What Price Culture? – A Taxonomy of the Admission Pricing Policy at Museums - Althaus, Maike; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (International Journal of Cultural Policy)
An admission pricing policy should allow a museum to facilitate access to cultural education and heritage while contributing to its economical sustainability. Despite the importance of this matter to museums, design-relevant knowledge on the configuration of the admission pricing policy in museums remains limited, resulting in museum decision-makers lack the necessary understanding of how to customize their admission pricing policy, and researchers the foundation for advancing knowledge on the topic. To address these issues, we draw on a well-established development method to build a taxonomy, which involved synthesising the literature on the admission pricing policy of museums, analysing the characteristics of the admission pricing policy of 149 museums, and creating a cluster analysis for 117 museums located in the same region. The analysis yielded three distinct clusters (namely, free admission pricing policy, simple admission pricing policy, comprehensive admission pricing policy). Our work supports practitioners by showing them different options for structuring an admission pricing policy, while providing researchers with a foundation for further investigating museums’ admission pricing policies.

§ 16 a (Girokonto und Zahlungsdiensterahmenvertrag) - Bartlitz, David (Verbraucherrecht)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

„Allowing the Economy to Breathe Even During the Crisis“ – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert (german research – Magazine of the Deutsche Forschungsgemeinschaft)

„Go with the flow?!“ Einblicke in Forschungsansatz und erste Ergebnisse des Begleitforschungsprojekts ITiB - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

“Sorry, Too Much Information”. Designing Online Review Systems that Support Information Search and Processing - Seutter, Janina; Kutzner, K.; Stadtländer, M.; Kundisch, Dennis; Knackstedt, R. (Electronic Markets)

„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

#DIGITALENTS - Digital Talents Programm geht in die zweite Runde - Kundisch, Dennis

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A combinatorial data envelopment analysis with uncertain interval data with application to ICT evaluation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Technological Forecasting and Social Change)
Keywords: Management of Technology and Innovation; Applied Psychology; Business and International Management

A comparative performance analysis of intelligence-based algorithms for optimizing competitive facility location problems - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Tavana, Madjid; Santos-Arteaga, Francisco J.; Hosseinzadeh, Sanaz (Machine Learning with Applications)
Keywords: General Medicine